Adipose‐Derived Biogenic Nanoparticles for Suppression of Inflammation. Issue 10 (18th February 2020) - Tian, Ming; Ticer, Taylor; Wang, Qikun; Walker, Sierra; Pham, Anthony; Suh, Annie; Busatto, Sara; Davidovich, Irina; Al‐Kharboosh, Rawan; Lewis‐Tuffin, Laura; Ji, Baoan; Quinones‐Hinojosa, Alfredo; et al.
Abstract: Extracellular vesicles secreted from adipose‐derived mesenchymal stem cells (ADSCs) have therapeutic effects in inflammatory diseases. However, production of extracellular vesicles (EVs) from ADSCs is costly, inefficient, and time consuming. The anti‐inflammatory properties of adipose tissue‐derived EVs and other biogenic nanoparticles have not been explored. In this study, biogenic nanoparticles are obtained directly from lipoaspirate, an easily accessible and abundant source of biological material. Compared to ADSC‐EVs, lipoaspirate nanoparticles (Lipo‐NPs) take less time to process (hours compared to months) and cost less to produce (clinical‐grade cell culture facilities are not required). The physicochemical characteristics and anti‐inflammatory properties of Lipo‐NPs are evaluated and compared to those of patient‐matched ADSC‐EVs. Moreover, guanabenz loading in Lipo‐NPs is evaluated for enhanced anti‐inflammatory effects. Apolipoprotein E and glycerolipids are enriched in Lipo‐NPs compared to ADSC‐EVs. Additionally, the uptake of Lipo‐NPs in hepatocytes and macrophages is higher. Lipo‐NPs and ADSC‐EVs have comparable protective and anti‐inflammatory effects. Specifically, Lipo‐NPs reduce toll‐like receptor 4‐induced secretion of inflammatory cytokines in macrophages. Guanabenz‐loaded Lipo‐NPs further suppress inflammatory pathways, suggesting that this combination therapy can have promising applications for inflammatory diseases. Abstract : Extracellular vesicles (EVs) released from adipose‐derived mesenchymal stem cells (ADSCs) have therapeutic effects in inflammatory diseases. However, production of EVs from ADSCs is inefficient. The anti‐inflammatory properties of adipose tissue‐derived EVs and other biogenic nanoparticles (BiNPs) obtained directly from lipoaspirate (Lipo) are evaluated and compared to those of ADSC‐EVs. Moreover, guanabenz (GBZ) loading in Lipo‐NPs is assessed for enhanced anti‐inflammatory effects.